First case of Zika virus infection during an outbreak of chikungunya in a rural region of Maharashtra state, India. (12th April 2022) - Gurav, Yogesh K; Alagarasu, Kalichamy; Yadav, Pragya D; Sapkal, Gajanan; Gokhale, Mangesh; Parashar, Deepti; Jadhav, Ujwala; Bote, Minal; Kakade, Mahadeo; Nyayanit, Dimpal; Kumar, Abhinendra; Deshpande, Gururaj Rao; et al.
Abstract: Background: In July 2021, an outbreak of chikungunya virus (CHIKV) was reported in a rural region of Maharashtra state, India. Methods: Serum samples of symptomatic cases (n=33) were screened for dengue virus (DENV), CHIKV and Zika virus (ZIKV) by molecular and serological assays. Results: The first case of ZIKV infection from Maharashtra was detected and confirmed by molecular and serological assays. Complete genome sequencing revealed that the ZIKV sequence belongs to the Asian genotype and had a closer homology with pre-epidemic strains present before 2007. Conclusions: ZIKV surveillance needs to be strengthened in the regions experiencing dengue and chikungunya outbreaks.